2002
DOI: 10.1111/j.1572-0241.2002.05551.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autonomic Dysfunction in Cirrhotic and Noncirrhotic Portal Hypertension

Abstract: Autonomic dysfunction is frequently encountered in patients with EHPVO and cirrhosis, and the presence of autonomic dysfunction in patients with noncirrhotic portal hypertension suggests a primary role of portal hypertension per se in the dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[92]. Portal hypertensive gastropathy is relatively less common in NCPF [57] than in cirrhosis and manifests mainly after variceal obliteration. Anorectal varices are more common in NCPF than in cirrhosis.…”
Section: Prevalence Of Varicesmentioning
confidence: 98%
See 1 more Smart Citation
“…[92]. Portal hypertensive gastropathy is relatively less common in NCPF [57] than in cirrhosis and manifests mainly after variceal obliteration. Anorectal varices are more common in NCPF than in cirrhosis.…”
Section: Prevalence Of Varicesmentioning
confidence: 98%
“…Consensus statements Left upper quadrant pain due to perisplenitis and splenic infarction is not uncommon [53]. Like cirrhosis, NCPF also may have odd presentations, such as glomerulonephritis [54,55], hypoxemia [56], or autonomic dysfunction [57]. [7].…”
Section: Repeated Low-dose Endotoxemia Of Portal Circulationmentioning
confidence: 99%
“…Since the autonomic nervous system directly innervates the hepatic parenchyma and has a role in metabolic control [3], it seems likely that liver regeneration and apoptosis are cooperatively regulated by both humoral factors and the autonomic nervous system. Moreover, it is well known that autonomic abnormalities and neuropathy tend to increase with age [4]. The prevalence and severity of autonomic dysfunction appears to be related to the severity of liver disease and is associated with an increase in mortality [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Vagal afferent and efferent fibers also innervate the portal vein, hepatic arteries, and biliary ducts in addition to liver parenchyma 24. Specifically, autonomic dysfunction has been observed in the setting of portal hypertension1, 2, 3 and nonalcoholic fatty liver disease,25 and denervation of liver parenchyma has been observed in cirrhosis 26. Cardiac metaiodobenzylguanidine studies have shown an increased washout rate consistent with abnormal myocardial norepinephrine reuptake in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liver disease can affect circulating inflammatory peptides and lead to autonomic dysfunction, creating a proarrhythmic substrate 1, 2, 3, 4. An elevated risk of atrial fibrillation (AF) among patients with liver disease and structurally normal hearts seems plausible given that inflammation and autonomic dysfunction have been shown to contribute to pathogenesis of AF 5.…”
mentioning
confidence: 99%